CRP1 Protein: (dis)similarities between Arabidopsis thaliana and Zea mays - Ferrari, Roberto; Tadini, Luca; Moratti, Fabio; Lehniger, Marie-Kristin; Costa, Alex; Rossi, Fabio; Colombo, Monica; Masiero, Simona; Schmitz-Linneweber, Christian; Pesaresi, Paolo (Frontiers in Plant Science, 2017)
Biogenesis of chloroplasts in higher plants is initiated from proplastids, and involves a series of processes by which a plastid able to perform photosynthesis, to synthesize amino acids, lipids, and phytohormones is formed. All plastid protein complexes are composed of subunits encoded by the nucleus and chloroplast genomes, which require a coordinated gene expression to produce the correct concentrations of organellar proteins and to maintain organelle function. To achieve this, hundreds of nucleus-encoded factors are imported into the chloroplast to control plastid gene expression. Among these factors, members of the Pentatricopeptide Repeat (PPR) containing protein family have emerged as key regulators of the organellar post–transcriptional processing. PPR proteins represent a large family in plants, and the extent to which PPR functions are conserved between dicots and monocots deserves evaluation, in light of differences in photosynthetic metabolism (C3 vs. C4) and localization of chloroplast biogenesis (mesophyll vs. bundle sheath cells). In this work we investigated the role played in the process of chloroplast biogenesis by At5g42310, a member of the Arabidopsis PPR family which we here refer to as AtCRP1 (Chloroplast RNA Processing 1), providing a comparison with the orthologous ZmCRP1 protein from Zea mays. Loss-of-function atcrp1 mutants are characterized by yellow-albinotic cotyledons and leaves owing to defects in the accumulation of subunits of the thylakoid protein complexes. As in the case of ZmCRP1, AtCRP1 associates with the 5′ UTRs of both psaC and, albeit very weakly, petA transcripts, indicating that the role of CRP1 as regulator of chloroplast protein synthesis has been conserved between maize and Arabidopsis. AtCRP1 also interacts with the petB-petD intergenic region and is required for the generation of petB and petD monocistronic RNAs. A similar role has been also attributed to ZmCRP1, although the direct interaction of ZmCRP1 with the petB-petD intergenic region has never been reported, which could indicate that AtCRP1 and ZmCRP1 differ, in part, in their plastid RNA targets.